Community Empowerment Through the Development of Interactive Pop-Up Book Media as a Creative Learning Tool for Early Childhood Education - Zhilli Izzadati Khairuni; Siti Zulfa Yuzni; Liana Atika; Wahyu Hutria; Mita Dwi Putri; Mirzal Yacub; Ahmad Zulfikar; Khairunnisak Khairunnisak; Wisnu Prayogo (Carmin: Journal of Community Service, 2026)
Community empowerment through creative education can strengthen teachers' capacity to independently develop contextual and accessible learning media, particularly for early childhood settings where engaging, hands-on resources are essential. This community service program aimed to develop and implement interactive pop-up books as creative learning tools while strengthening teachers' capacity to design, produce, and utilize visual learning media for early childhood education. The program was conducted at RA Nadhira Asy Syafa, Deli Serdang Regency, Indonesia, employing participatory, educational, and practical approaches. Teachers were actively involved throughout the process, including problem identification, theme selection, media design, production, classroom implementation, and evaluation, ensuring that the resulting media reflected both pedagogical needs and local context. Data were collected through observation, interviews, discussions, documentation, and a simple response questionnaire structured around four indicators: student engagement, early reading responses, creativity, and perceived support of pop-up books for learning. The findings revealed generally positive responses to the developed media. Specifically, 66.7% of respondents agreed or strongly agreed that the media supported student engagement and early reading responses, while 91.7% reported positive perceptions of children's creativity, and 91.7% agreed or strongly agreed that the pop-up books effectively supported learning activities. Nevertheless, variations in children's responses suggest that continued teacher guidance and adaptation to individual developmental needs remain necessary for optimal outcomes. Overall, the program demonstrates that collaboratively developed pop-up books can serve as accessible, low-cost, and context-sensitive learning media, while simultaneously strengthening teachers' practical capacity to independently design and produce creative educational materials suited to their classroom needs.